Cross-National and Comparative History of Science Education: An Introduction (2013)
The history of science, technology and medicine is currently attempting to move towards the global, attuned to the resonance of buzzwords such as 'globalization' and 'transnationalism' in the affairs of our times.1 In the last decades, social construc- tivism2 has had a fundamental role in the shaping of our discipline, but it has also contributed to consecrating the local against the global. As a reaction to positivism, social constructivism converted the making of any generalization in a national or international scale into anathema. In considering that science was not universal, the field moved towards the production of microhistories that, while illuminating the role of social processes in the construction of scientific knowledge in local settings, have also obscured the relevance of macrohistorical explanations.3 Paradoxically, social constructivists, like their predecessors, gave an implicit status of universality to a set of categories, in their case stressing the locality of knowledge.But there are obviously other reasons for the discrimination of the global against the local. A decade ago Lewis Pyenson predicted the end of national science and the rise of comparative history,4 but in fact our field is still characterized by national pictures (or local cases which explicitly or implicitly are endowed with national qualities). There are still a small number of historical studies which deal with sci- ence, technology and medicine in more than one national context.5 In practical terms this is understandable, since tackling several national cases in comparative or cross- national perspective is not a simple matter, and is hindered by demanding knowledge of several languages and national historiographies, and the infrastructure required to work in archives and collections in different countries.However, there is a clear interest in our field to move beyond the local, which has in general taken alternative and complementary ways to comparative history. New approaches have focused their attention on the study of international connections through mediating agents (human and non-human) and the analysis of knowledge circulation between different national or cultural contexts. James Secord's program- matic proposal 'Knowledge in transit' and Schaffer, Roberts, Raj and Delbourgo's advocacy for the study of 'go-betweens' in The brokered world are two of the most representative and recent proposals in this field.6 In spite of their novelty, these approaches have many things in common with proposals previously developed in history of science and in other historical specialisms. Examples of these are the study of 'travels of learning', circulation and appropriation by the group STEP (Science and Technology in the European Periphery), the focus on cultural transfers and mediating agents applied in cultural and book history, and the study of cultural 'passeurs' and transnational interactions in Latin American and Atlantic history.7While these approaches are contributing decisively to a more accurate assessment of the role of international and transnational phenomena, they involve the risk - if applied alone - of circumventing the important role of the nation in science. A combination of approaches in cross-national perspective is required, which acknowledges national, international and transnational phenomena in their proper measure.8 This special issue intends to contribute to this critical question by presenting a series of studies in cross-national history of science education.Cross-national comparison was a major driving force in the nineteenth-century organization of science and education. Educationists, scientists and students circulated across national boundaries and compared different educational systems, producing accounts which contributed to inform educational reforms in their own national or local contexts. The development of national systems of education and examination, in which the sciences were taught in a systematic manner for the first time and the publics of science expanded dramatically, had a major role in the shaping of scientific disciplines and medical specialities.